FINANCING AFFORDABLE HEALTH CARE A MINNESOTA CITIZENS FOR TAX JUSTICE REPORT - COX,W (Tufts Archival Research Center, 2007)
Report evaluating the MinnesotaCare health access and cost containment program in terms of progress goals. Lists possible financing mechanisms. Provides background information on program, particularly on eligibility and financing, particularly on proposed cigarette tax increases. Argues that no new taxes are needed to provide coverage to families with children up to 150% of poverty. Agrees that taxes are needed to reach legislated goal of 275% of poverty, but progressive taxes should be instated.